Analisis Pengaruh Kompetensi Dosen Terhadap Preferensi Mahasiswa Pada Profesi Akuntan (Studi Kasus Pada PTS Di Surakarta) - Henstin Mutmainah; Rosita Rosita (Universitas Muhammadiyah Metro, 2017)
This study aims to determine the effect of capabilities of lecturers (teachers) that can affect student preferences in the profession as an accountant. Benefits of the research was to determine the factors of capabilities that can make the students make the selection of the accounting profession. Factors capability in terms of the competence of lecturers (the questionnaire can be processed. Testing the validity, reliability and classical assumption produce reliable data for use in the research model. The model was tested using multiple regression techniques (multiple regresion).The results of the research that is of no significance of factors of capability of lecturers consisting of pedagogical competence, personal competence, social competence and professional competence of the students choose the profession as an accountant. It can be said that the great competence of lecturers can not lead students to choose accounting profession.As a research suggestion would be better if there is a variable in the factor of competence with a preference in the selection of the profession by students.teachers) under Law No. 14 of 2005 which is pedagogical, personal competence, social competence and professional competence.This study collected data relating to the object to be used as a sample that is data on PTS Surakarta students who take the program S1 Accounting. Observation and questionnaires conducted with 100 questionnaires with a return rate of 100% and all the results of Keywords: capability, lecturers, preference, profession, accountants